Temperature dependent behaviour of lead sulfide quantum dot solar cells and films. Issue 9 (17th August 2016) - Speirs, Mark J.; Dirin, Dmitry N.; Abdu-Aguye, Mustapha; Balazs, Daniel M.; Kovalenko, Maksym V.; Loi, Maria Antonietta
Abstract : The temperature dependent behaviour of PbS QD solar cells and thin films was investigated, and guidelines for further improvement of the power conversion efficiency are given. Abstract : Despite increasing greatly in power conversion efficiency in recent times, lead sulfide quantum dot (PbS QD) solar cells still suffer from a low open circuit voltage ( V OC ) and fill factor (FF). In this work, we explore the temperature dependent behavior of ∼9% efficient solar cells. In the temperature range of 290 to 230 K, we find increased V OC and FF values without significant degradation of the short circuit current, leading to up to 10.3% efficiency at 230 K. The change in V OC is driven by the decrease of the reverse saturation current which fits the PN-junction model. Using Schottky and single carrier devices, we measure the carrier mobility, diffusion lengths, and doping concentrations of PbS QD films with tetrabutylammonium iodide and ethane dithiol ligands as a function of temperature. Both mobility and diffusion length are found to decrease with decreasing temperature while device performance increases, indicating that the 260 nm thick active layer is fully depleted. Finally, we propose that further optimization of the doping concentrations could help achieve increased device performance at room temperature.